Análisis de la variación genética en Piaractus brachypomus (Pisces, Characidae) en estaciones piscícolas colombianas mediante RAPD (2004)
ABSTRACT: Information on genetic variation in cultured fish species is essential for an appropriate animal management both in the wild and in captivity. In this study was used the Random Amplified Polymorphic DNA (RAPD) to evaluate the genetic variation in juveniles of Piaractus brachypomus (Characiformes, Characidae, Serrasalminae) from four hatcheries located near Villavicencio, Meta department (eastern Colombia). It were considered as an intra specific control, the progeny of broodstocks from the wild, and as an inter specific controls were used the individuals of the family Characidae; Colossoma macropomum, of the subfamily Serrasalminae and Brycon moorei of the subfamily Bryconinae. Thirty four out of forty RAPD primers, kits OPA and OPB with 20 primers each (10 nucleotides per primer), yielded 1168 amplified fragments of DNA, of which 440 were unique fragments that discriminated among individuals in this study. The Genetic Distance (DG) showed that juveniles of Piaractus brachypomus had a lower distance respect to the intra specific control from the wild, suggesting a decrease genetic variation manifested in a lower number of unique fragments. Possibly caused by the use of the same broodstock confined, no renewed, in the reproductive zones. Anthropogenic effects in the region such as the water pollution by agrochemicals, the overfishing, the deforestation and the river sedimentation have decreased the individuals number in the fishing zones, forcing farmers to have a reduced broodstock numbers. Colossoma macropomum and Brycon moorei got apart from the Piaractus brachypomus cluster, giving validity to the taxonomic classification, as different species.